Safer prescribing and monitoring of high‐risk medicines - Wood, Su (Prescriber (London, England), 2020)
General practice is now responsible for prescribing more high‐risk medicines with regular monitoring requirements. This article discusses some of the medicines that require more intensive monitoring, and the systems Primary Care Networks can put in place to ensure safer prescribing of these medicines.